Agrarian Conflicts After the Establishment of the Land Bank Agency in Indonesia - Permadi, Iwan; Fadhli Rahman Arif (Fakultas Hukum Universitas Muhammadiyah Sorong, 2025)
The establishment of the Land Bank in Indonesia may lead to conflicts of interest and the existence of customary land may be forgotten for reasons of land stateisation. The process of acquiring customary land for reasons of stateisation may affect the legal protection of indigenous peoples' rights. This article examines agrarian conflicts after the establishment of the Land Bank Agency and the legal protection of indigenous peoples' land. This research is examined using the normative juridical method with a statutory approach. The results of the study found that the concept of the Land Bank is in contrast to agrarian reform in terms of land acquisition operations, because land can be obtained through the transfer of land ownership by the state which is intended for investment and infrastructure development. The government needs to improve the land sector Job Creation Law and the legal regulations of the Land Bank, the government must revise the rules related to the Land Bank so that this institution can maintain a balance of land utilisation for various interests fairly. The Land Bank should be a representative of the state to protect vulnerable groups of people, one of which is indigenous peoples. Then the community must be pro-active in applying for a Material Test on articles that have negative potential, especially the regulation of land stateisation in the Job Creation Law and the legal rules regarding the Land Bank in an effort to consolidate guarantees and justifications for land rights over indigenous peoples.